The Quality of Chicken Nuggets With Addition Gouda Cheese (Faculty of Animal Science Universitas Brawijaya, 2010)
The objective of this research was to acquired the best percentage of using cheese in the chicken nuggets processing. Materials used for this research were nuggets made from chicken meat, Gouda cheese and spices. Experiment done with Random Block Analysis as experiment design by addition Gouda Cheese ( 0% (F0), 5% (F1), 10% (F2), 15% (F3), 20% (F4) ). The results showed that chicken nuggets with Gouda cheese addition gave a highly significant effect (P<0.01) on mouisture, fat, protein, ash contents, texture and WHC, and addition gave a non significant effect (P>0.05) on pH and Organoleptic. The best result was nuggets which made with addition of 15 percent of Gouda cheese.The conclusion of this research was the addition of Gouda Cheese to Chiken Nuggets increased fat content, protein content, ash content, WHC and tend to decreased mouistured content, textured. Result of panelist not trained using cheese in manner chicken nuggets are like made with addition of 15 percent of Gouda cheese. The best result was nuggets which made with addition of 15 percent of Gouda chees Keywords : Chicken nuggets, Chicken meat, Gouda cheese